2007
DOI: 10.1002/ange.200701733
|View full text |Cite
|
Sign up to set email alerts
|

Charge‐Transfer‐Chromophore durch Cycloaddition‐Retro‐Elektrocyclisierung: multivalente Systeme und Kaskadenreaktionen

Abstract: Eine ähnliche Reaktion tritt bei umgekehrten elektronischen Verhältnissen auf: Hopf und Mitarbeiter zeigten, dass der starke Elektronendonor Tetrathiafulvalen (TTF) eine Cycloaddition mit elektronenarmen Acetylen-Einheiten in Cyanethinylethenen eingeht, wobei die anschließende elek-[4] Eine gleichartige Reaktion wurde von Hirsch und Mitarbeitern an terminalen AcetylenEinheiten von a,w-Dicyanpolyinen beobachtet. [5] Hier beschreiben wir die Anwendung der Reaktion von TCNE mit elektronenreichen Alkinen zur hoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 30 publications
2
41
0
3
Order By: Relevance
“…[10] NMR spectroscopy revealed the co-existence of different conformers at room temperature, which converged to a single species upon heating to 100 8C. In accordance to previous studies, [13] slow interconversion of similar dendralenes at room temperature is a consequence of steric crowding.…”
supporting
confidence: 83%
“…[10] NMR spectroscopy revealed the co-existence of different conformers at room temperature, which converged to a single species upon heating to 100 8C. In accordance to previous studies, [13] slow interconversion of similar dendralenes at room temperature is a consequence of steric crowding.…”
supporting
confidence: 83%
“…Electrochemical investigations revealed that dendritic donor-substituted TCBDs undergo multiple redox steps at virtually matching potentials, [7] which suggests that the individual electron donor and acceptor moieties behave as independent electroactive centers. [12] This behavior has previously also been observed for ferrocenyl dendrimers by Astruc and co-workers [10] and by others.…”
Section: Resultsmentioning
confidence: 99%
“…[20] This is in very good agreement with the markedly lower first-oxidation potential of 7 (+ 0.41 V in CH 2 Cl 2 versus Fc + /Fc (ferricinium/ferrocene couple)) compared with 5 and 6 (+ 0.88 and + 0.89 V in CH 2 Cl 2 versus Fc + /Fc, respectively; see the Supporting Information). [7] The first-oxidation potential of 7, however, is considerably higher than that of 14, which is approximately À0.30 V in MeCN (versus Fc + /Fc) ( Figure 5). [21] Thus, a considerable interaction of the vinylogous tetrathiafulvalene-type donor with the 1,1,4,4-tetracyanobuta-1,3-dienyl moiety exists.…”
Section: Oxidation Of 2 With [Bis(trifluoroacetoxy)iodoa C H T U N G mentioning
confidence: 96%
See 1 more Smart Citation
“…The protocol was adopted by several other groups using THF as a cosolvent with beneficial results [119]. Other common cosolvents include DMF [55,63], NMP (N-methylpyrrolidinone) [34,54,82,92], benzene [120], and toluene [62,78,121]. Although in many cases an increase in the solubility of catalysts, reactants, and products appeared to be a major factor [122], there is no detailed explanation for the observed reaction improvements due to solvent effects.…”
Section: Solvents and Additivesmentioning
confidence: 99%